Identidade em social network games: a construção da identidade virtual do jogador do FarmVille e do SongPop - Rebs, Rebeca da Cunha Recuero (Universidade do Vale do Rio dos Sinos, 2014)
This thesis begins with the recognition that social network games offer spaces for participants to reflect on their identities. In them, users identify themselves and shape their profiles to be recognized and to interact with other players. Our objective focuses on understanding how these identities are configured and how they reflect the gamer in their own games. The theoretical discussion includes key concepts such as identity and online games, the visualisation of identities in cyberspace, the forms online games and cultural mediations take and the technical skills related to these games. The social network games were contextualized from their social and historical aspects, present situation, media environments and dynamic possibilities. Our empirical research is grounded on a construction of types of games based on terms of possibilities for identity construction, which includes "World Construction" games that stimulate the customization of environments and "World Participation" games, which encourage competition with actors of the social network. We chose to use a netnography methodology, developed in games within each category: Farmville and SongPop (respectively), as well as interviews with a sample of players. The results show the existence of elements in the game that are able to offer places to the development of social appropriation (avatars, virtual goods, social interactions and virtual territory), indicators of identity facets of these subjects. Through them, we realized the existence of identity matrices in social network games (random, competitive, descriptive and evaluative) capable of directing the way individual and collective construct these subjects even before they have contact with these appropriation places in the games. The implications of this study reveal the existence of two ways of affecting users that arises not only from the structure of the games, but mainly from creative spaces where subjects manifest their identities. Through them, the social gamers not only reveal traces of themselves, but also seem to incorporate new identity facets of these constructs derived in the game to their self, which suggests an important role of these ludic and virtual environments in the identity constitution of the subject.
Keywords: Identidade; Identidade virtual; Jogos online; Social network games; Jogos de sites de redes sociais; Identity; Virtual identity; Online games; Social networking sites; ACCNPQ::Ciências Sociais Aplicadas::Comunicação